Assessment of behavioral factors associated with dental caries in pre-school children of high socioeconomic status families - Bushra Rashid Noaman (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Many Iraqi children of high socioeconomic status (SES) families attend dental clinics presenting predominantly cavitated and painful multiple carious lesions. The factors responsible for dental caries within this sector of society need to be identified. Purpose: The aim of this study is to assess the dental care behavior of mothers and its relationship with the prevalence of dental caries in pre-school age children drawn from high SES families in northern Iraq. Methods: A study was conducted to assess the prevalence of dental caries and its relationship to oral hygiene habits in 440 pre-schoolers living in Erbil, northern Iraq. An oral hygiene questionnaire was distributed among the families. Dental examination of the children was performed to calculate the dependent factor of decayed, missing and filled teeth due to caries (dmf). All data was analyzed by means of the SPSS Microsoft statistical system using descriptive tables to identify the relationship between the dependent and independent variable dmf indexes. In order to find the significances, a Chi-square test, a Fisher’s exact test and a likelihood ratio test were used at level of p<0.05. Results: 67% of the children in the sample had dental caries (mean dmf=3.25±3.77) with 5-year-olds being more affected by dental caries (74%) than 4-year-olds (60%). A strong correlation was found in this study between the dependent factor, dmf, and the following independent factors: frequency of snack consumption, the need to assist the child during brushing, maternal caries and the mother’s education. Conclusion: Despite being members of high SES families, the children examined were significantly subject to dental caries, a fact directly correlated with inappropriate behavior on the part of their caregivers in relation to the essential aspects of oral health care.